Android Based Chemical Reaction Learning, Capturing Chemical Substances (Tazami): Pembelajaran Reaksi Zat Kimia Berbasis Android, Tangkap Zat Kimia (Tazami) - Dianti Bintari, Evi; Fitria, Fitria (Universitas Muhammadiyah Sidoarjo, 2019)
The purpose of this research is to create a Tazami Game made from the basis of mobile use in filling spare time. Periodic table of chemistry as a basic reference of all these chemicals. The periodic table itself can be easily searched on the internet and various other sources. The method used carries the concept of a more interactive game education. With the input of chemical data as collectible items. Some chemicals are taken in the category of suitability and function as items that must be collected. Psychological effects become side effects felt by players through the effects of impact, meaning that the player unconsciously learns through the game being played. The results of the trial using the black box test technique means to test the buttons and panels that require that the system be made in accordance with the concept. Trying to produce a system in accordance with the concept made. Animated motion on the interface and gameplay, matching the flow of the panel on the button, until the chemical data input is in accordance with the concept. In the conclusion there are no errors, bugs, or other fatal mistakes.